Programas de diversidade de recursos humanos: uma análise sobre sua adoção no Brasil - Reith, Stefanie Landim (Universidade Federal de São Carlos, 2014)
The purpose of this master´s degree thesis is to analyze the adoption of diversity programs for inclusion of women and blacks in companies in Brazil. We chose to conduct the survey on companies listed on the ranking "Melhores Empresas para Você Trabalhar" (Best Companies to Work For), in which they participate for human resources management practices evaluated as advanced. Few companies have diversity programs, but more than indicated by the literature review. Most programs are in initial stages. It was also possible to observe the relationship of the adoption of these programs with the size and origin of the capital of the companies surveyed.
Keywords: Recursos humanos; Diversidade no local de trabalho; Gestão de pessoas; Gênero; Raça; Discriminação; Mercado de trabalho; Diversity of human resources; Management; Gender; Race; Labor market; Discrimination; ENGENHARIAS::ENGENHARIA DE PRODUCAO